An Update to Dialysis-Based Drug Release Testing-Data Analysis and Validation Using the Pharma Test Dispersion Releaser - Marc-Phillip Mast; Harshvardhan Modh; Julian Knoll; Elena Fecioru; Matthias G. Wacker (MDPI AG, 2021)
Currently, a wide variety of complex non-oral dosage forms are entering the global healthcare market. Although many assays have been described in recent research, harmonized procedures and standards for testing their in vitro performance remain widely unexplored. Among others, dialysis-based techniques such as the Pharma Test Dispersion Releaser are developed for testing the release of drugs from nanoparticles, liposomes, or extracellular vesicle preparations. Here, we provide advanced strategies and practical advice for the development and validation of dialysis-based techniques, including documentation, analysis, and interpretation of the raw data. For this purpose, key parameters of the release assay, including the hydrodynamics in the device at different stirring rates, the selectivity for particles and molecules, as well as the effect of excipients on drug permeation were investigated. At the highest stirring rate, a more than twofold increase in the membrane permeation rate (from 0.99 × 10−3 to 2.17 × 10−3 cm2/h) was observed. Additionally, we designed a novel computer model to identify important quality parameters of the dialysis experiment and to calculate error-corrected release profiles. Two hydrophilic creams of diclofenac, Voltaren® Emulgel, and Olfen® gel, were tested and provide first-hand evidence of the robustness of the assay in the presence of semisolid dosage forms.